ANALISIS KESULITAN BELAJAR SISWA PADA PEMBELAJARAN TEMATIK DI MASA PANDEMI COVID-19 DI KELAS IV SEKOLAH DASAR NEGERI 39 PONTIANAK KOTA, - Veneranda, Novika Reka; Halidjah, Siti; Vilda Ghasya, Dyoty Auliya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research is entitled "Analysis of Student Learning Difficulties in Thematic Learning During the Covid-19 Pandemic in Class IV SDN 39 Pontianak Kota". The background of this research is that fourth grade students at SDN 39 Pontianak City experience learning difficulties in thematic learning. Learning difficulty is a symptom that appears in students which is characterized by the presence of low learning outcomes or below predetermined standards. This research is a qualitative descriptive study. The data obtained from this study used observation, interviews with teachers, students and parents as well as documentation. The results of this study reveal how students' learning difficulties in thematic learning during the Covid-19 pandemic and the factors that influence it. Students show inappropriate attitudes (social), low student academic achievement (academic), difficulty making new understandings (metacognition), students are slow in processing something (processing speed), students have difficulty interpreting what is felt, heard, and seen (perception) , students are less attentive and less focused on learning (attention), too many activities that are not useful for students to do so it is difficult to remember the subject matter (memory). Factors that cause students to experience learning difficulties are internal factors and external factors. Internal factors that influence it are lack of attention in learning (concentration), lack of participation and response of students when participating in teaching and learning activities (reactions), slowness of students in understanding the material (comprehension), and incomplete test scores (repeat). While the external factors that influence it are the influence of friends in the community (social environment).